Pengaruh Disiplin Kerja, Komitmen Dan Budaya Organisasi Terhadap Kinerja Pegawai Pada Sekertariat Daerah Kabupaten Kolaka - Usman, Usman; Sulistia, Wiwi; Hatani, La; Rommy, Nursaban (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
This study aims to examine and explain the influence of work discipline, organizational commitment, and organizational culture on employee performance, both simultaneously and partially. The research adopts a quantitative approach with a cross-sectional design, emphasizing observational and investigative data to obtain an objective understanding of the relationships among the studied variables. Data were collected through a structured questionnaire distributed to all employees of the Regional Secretariat of Kolaka Regency. The population of this study consisted of 106 employees. Given the relatively small population size, a census method was applied, in which all members of the population were included as research respondents to ensure comprehensive and representative data. The collected data were analyzed using Multivariate Regression Analysis to determine the effects of work discipline, organizational commitment, and organizational culture on employee performance. The results indicate that work discipline, organizational commitment, and organizational culture simultaneously have a positive and significant effect on employee performance. Partially, work discipline has a positive and significant influence on employee performance, suggesting that employee compliance with organizational rules and work standards contributes to improved performance. Organizational commitment also shows a positive and significant effect on employee performance, reflecting that employee loyalty and attachment to the organization play an important role in enhancing performance. Furthermore, a supportive organizational culture provides a meaningful contribution to improving employee performance. Therefore, it can be concluded that improvements in work discipline, organizational commitment, and organizational culture lead to higher employee performance.